Role of Interface Design: A Comparison of Different Online Learning System Designs - Shi, Aiqin; Huo, Faren; Han, Dongnan (Frontiers in Psychology, 2021)
Mobile devices are becoming an indispensable part of daily lives and learning among older adults with the easy access of Internet. It enhances the connection between old users and online education, which supplied an approach to cultivate them with innovative concept and entrepreneurship education. However, the complicated navigation of information systems (IS) confused older adults, and get them disoriented in searches of information. In addition, influences online activities for older adults. This study aims to investigate what kind of navigation of information systems is suitable for older adults. A 2 X 2(2 factors, 2 levels) mixed experimental design was employed. Two factors are respectively cognitive load and navigation structure. A sample of 40 older participants (mean age=64.37, SD=4.03) performed online learning tasks in terms of innovative concept using linear hierarchical or mixed navigation structures under different time pressure. The results showed that linear hierarchical navigation is more appropriate for the elderly when learning and generate innovative concept on smartphones, the interaction between cognitive load and navigation structure exists. Overall, the findings combined suggest that the linear hierarchical navigation structure, compared to mixed hierarchical navigation, obtained better usability in terms of task efficiency, cognitive load and subjective ratings. The findings can provide theoretical supports for designers to design and develop mobile websites for older adults.